A Screen Method for the Mass-Production of the Small-Size and Side-View LED Package - Wen-Ray Chen; You-Sheng Luo (Crystals, 2018)
In this study, the small-size and side-view LED packages used in the backlight modules were examined by performing the electrostatic discharge (ESD) process. The high voltages used for the ESD process were 2 kV, 3 kV, and 4 kV. After ESD, the current–voltage curves were scanned from −7 V to 3 V. It was found that the significant leakage currents were in the reverse bias of 4 V~7 V and also in the forward bias of 1 V~2.5 V for ESD-damaged LED chips. However, the phenomenon of a slight increase in current was not found for the non-damaged samples. In our study case, the screening conditions could be set at a bias of −7 V or 2.3 V and the current of 0.1 µA.